The construction, composition and rationale of immigrants' network: The support strategies of Ghanaian immigrants in Toronto, Canada. (27th October 2022) - Kyeremeh, Emmanuel; Arku, Godwin
Abstract: In this article, we investigate the construction, composition and rationale behind the personal networks of recent immigrants to Canada. Drawing on egocentric‐network analysis and interviews with 172 Ghanaian immigrants in Toronto, we reveal their networking strategies during their integration. First, we identify social locations that help create ties with different groups: workplaces and schools offer access to ties with non‐immigrants and other immigrants alike, while religious and ethnic organizations facilitate ties to co‐nationals (i.e., Ghanaians). Second, most individuals within immigrants' network are co‐nationals whose relationship began in Canada, followed by sustained transnational ties in the origin and diaspora and few ties with the non‐immigrant. The nature of this network is explained by examining the migration project of immigrants together with the context of reception in Canada, which suggests a desire by immigrants to stay in Canada and make Canada their second home. The implications of these findings are discussed.